Fiber-reinforced hard alloy as well as preparation method and application thereof
By dispersing cemented carbide fibers in the cemented carbide matrix and preparing fiber-reinforced carbide, the contradiction between hardness and toughness of cemented carbide is solved, the coordination of high hardness and good toughness is achieved, and its application field is broadened.
Patent Information
- Application Number
- CN202510152071.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-02-12
AI Technical Summary
There is a contradiction between hardness and toughness in fine and medium crystal carbides, resulting in reduced processing efficiency and quality, and are prone to cracking or rapid wear under high pressure and friction conditions.
Carbide fibers are used as toughening material and dispersed in the carbide matrix. The fiber-reinforced carbide is prepared through the sintering process to achieve the coordinated densification of the carbide matrix and fibers.
It achieves the coordination of high hardness and good toughness of cemented carbide, solves the contradiction between hardness and toughness of cemented carbide, broadens its application areas, and is suitable for fields such as geological ore drilling and molding under certain impact conditions.
Smart Images

Figure CN119592888A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cemented carbide, and in particular relates to a fiber-reinforced cemented carbide and a preparation method and application thereof. Background Art
[0002] According to the definition of the classification of cemented carbide grain size by the German Powder Metallurgy Branch, cemented carbide with a WC particle size of 0.8~1.3μm is fine-grained cemented carbide, and cemented carbide with a WC particle size of 1.3~2.5μm is medium-grained cemented carbide. These two types of cemented carbide are widely used in the fields of mining drilling, mold forming, etc. However, there is a certain contradiction between the hardness and toughness of the above two types of cemented carbide, that is, the hardness increases while the toughness decreases, and vice versa. When the hardness and toughness of cemented carbide do not match, it will directly affect the processing efficiency and quality. Moreover, in the process of mining drilling or mold forming, the tool or mold prepared by cemented carbide needs to withstand greater pressure and friction. If the hardness is too high and the toughness is insufficient, the tool or mold is prone to cracking, resulting in damage and reducing the service life; on the contrary, if the toughness is too high and the hardness is insufficient, the wear resistance is poor, which will also cause rapid wear of the tool or mold. Therefore, how to solve the contradiction between the hardness and toughness of fine and medium-grained cemented carbide is a problem that urgently needs to be solved in this field. Summary of the invention
[0003] The purpose of the present invention is to provide a fiber-reinforced cemented carbide and its preparation method and application. The present invention uses cemented carbide fiber as a toughening material, disperses it in a cemented carbide matrix of the same system to obtain a fiber-reinforced cemented carbide, which can achieve the coordinated densification of the two cemented carbides. The fiber-reinforced cemented carbide has both high hardness and good toughness, which solves the contradiction between hardness and toughness of fine and medium-grained cemented carbides, and can be used in the fields of mining drilling, mold forming, etc. under certain impact conditions.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a fiber-reinforced cemented carbide, comprising a cemented carbide matrix and cemented carbide fibers dispersed in the cemented carbide matrix; The raw materials for preparing the cemented carbide fiber include a first WC powder, a first Co powder and a modifier; The raw materials for preparing the cemented carbide substrate include a second WC powder and a second Co powder.
[0005] Preferably, the mass fraction of the cemented carbide fiber in the fiber-reinforced cemented carbide is 3%-30%; the diameter of the cemented carbide fiber is 0.05-0.5 mm, and the aspect ratio is 2-10.
[0006] Preferably, in terms of mass percentage, the content of the second Co powder in the raw material for preparing the cemented carbide substrate is 4.5% to 10%.
[0007] Preferably, the mass fraction of carbon in the second WC powder is 6.12%-6.15%; the particle size of the second WC powder is 0.8-3.5 μm; and the particle size of the second Co powder is 1.0-1.5 μm.
[0008] Preferably, in terms of mass percentage, the content of the first Co powder in the raw material for preparing the cemented carbide fiber is 1% to 5% more than the content of the second Co powder in the raw material for preparing the cemented carbide matrix; and the modifier is a rare earth oxide.
[0009] Preferably, the modifier includes at least one of samarium oxide, yttrium oxide and dysprosium oxide; and the content of the modifier in the raw material for preparing the cemented carbide fiber is 0.5% to 1.2% by mass.
[0010] Preferably, the mass fraction of carbon in the first WC powder is 0.02%-0.04% higher than that in the second WC powder; the particle size of the first WC powder is at least 0.5 μm larger than that of the second WC powder; and the particle size of the first Co powder is 1.0-1.5 μm.
[0011] The present invention provides a method for preparing the fiber-reinforced cemented carbide described in the above technical solution, comprising the following steps: The cemented carbide fiber is mixed with the cemented carbide matrix and sintered to obtain the fiber-reinforced cemented carbide.
[0012] Preferably, the sintering temperature is 1400-1450° C., the holding time is 30-90 min, and the pressure is 1-4 MPa.
[0013] The present invention provides the use of the fiber-reinforced cemented carbide described in the above technical solution or the fiber-reinforced cemented carbide obtained by the preparation method described in the above technical solution in mining drilling or mold forming.
[0014] The present invention provides a fiber-reinforced cemented carbide, comprising a cemented carbide matrix and cemented carbide fibers dispersed in the cemented carbide matrix; the raw materials for preparing the cemented carbide fibers include a first WC powder, a first Co powder and a modifier; the raw materials for preparing the cemented carbide matrix include a second WC powder and a second Co powder. In the present invention, WC powder and Co powder are necessary components for preparing cemented carbide, and the function of the modifier is to purify WC grain boundaries and strengthen cobalt and other bonding phases, which is beneficial to simultaneously improve the hardness and toughness of the obtained fiber-reinforced cemented carbide. The present invention adopts cemented carbide fibers as toughening materials, and disperses them in a cemented carbide matrix to obtain a fiber-reinforced cemented carbide; the cemented carbide fibers have high toughness and a fiber shape, and when microcracks in the cemented carbide matrix expand, the cracks will deflect or stop when encountering the cemented carbide fibers, that is, the cemented carbide fibers can hinder the expansion of cracks in the cemented carbide matrix to achieve toughening. At the same time, since both the cemented carbide fiber and the cemented carbide matrix belong to the WC-Co material system and have similar lattice constants, this similarity enables them to form a good lattice match at the interface, reducing the possibility of lattice distortion and stress concentration; in this case, the fiber-reinforced cemented carbide is prepared, which will not affect the original carbon control system standard, and can solve the problem that the grain boundary is prone to defects due to the mismatch of the interface of dissimilar materials, and can also improve the cemented carbide bonding force, reduce stress, and achieve the synergistic densification of cemented carbide fibers and cemented carbide matrix. The fiber-reinforced cemented carbide of the present invention has higher hardness and better toughness at the same time, solves the contradiction between the hardness and toughness of cemented carbide, and further broadens the application field of traditional cemented carbide. The fiber-reinforced cemented carbide of the present invention can be applied to the fields of mining drilling and mold forming under certain impact conditions.
[0015] Furthermore, the present invention uses cemented carbide fiber as a toughening material, which can reduce the amount of modifier in the fiber-reinforced cemented carbide to a certain extent. Moreover, since the cemented carbide fiber still belongs to the WC-Co system, it can promote the hardness and toughness of the fiber-reinforced cemented carbide without affecting the original carbon control system standard.
[0016] Furthermore, the present invention controls the interface composition gradient by adjusting the composition difference between the cemented carbide fiber and the cemented carbide matrix in the fiber-reinforced cemented carbide. Specifically, the cemented carbide fiber and the cemented carbide matrix having smaller differences in total carbon, WC particle size and Co content are matched so that stress is not generated at the interface due to the excessive difference mentioned above, and the purpose of synergistic densification and toughening of the two cemented carbides can be achieved, thereby avoiding the generation of pores. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0018] Figure 1 The following is a flow chart of preparing fiber-reinforced cemented carbide according to an embodiment of the present invention; Figure 2 This is a scanning electron microscope image of the fiber-reinforced cemented carbide obtained in Example 1; Figure 3 This is a scanning electron microscope image of the fiber reinforced cemented carbide obtained in Example 2. DETAILED DESCRIPTION
[0019] The present invention provides a fiber-reinforced cemented carbide, comprising a cemented carbide matrix and cemented carbide fibers dispersed in the cemented carbide matrix; The raw materials for preparing the cemented carbide fiber include a first WC powder, a first Co powder and a modifier; The raw materials for preparing the cemented carbide substrate include a second WC powder and a second Co powder.
[0020] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.
[0021] The fiber-reinforced cemented carbide of the present invention comprises a cemented carbide matrix, and the raw materials for preparing the cemented carbide matrix comprise a second WC powder and a second Co powder.
[0022] In terms of mass percentage, the content of the second Co powder in the raw material for preparing the cemented carbide substrate of the present invention can be 4.5% to 10%; in a specific embodiment of the present invention, the content of the second Co powder in the raw material for preparing the cemented carbide substrate is 6% or 8%. The particle size of the second Co powder of the present invention can be 1.0 to 1.5 μm; in a specific embodiment of the present invention, the particle size of the second Co powder is 1.0 μm, 1.2 μm or 1.5 μm.
[0023] The raw materials for preparing the cemented carbide matrix of the present invention also include a second additive. The second additive of the present invention may include carbon black, a molding agent and a dispersant; the molding agent may be paraffin; the dispersant may be anhydrous ethanol. In a specific embodiment of the present invention, the second additive includes carbon black, paraffin and anhydrous ethanol. The present invention has no special requirements on the particle size of the carbon black and paraffin, and conventional carbon black and paraffin in the art can be used. In the present invention, the role of carbon black is to supplement carbon for the second WC powder; the molding agent is to improve the pressing performance of the material, so that the material is pressed to form a compact with a certain strength, which has a certain effect on the shape and mechanical properties of the obtained cemented carbide matrix; the dispersant can improve the mixing uniformity between the materials, thereby promoting the improvement of the mechanical properties of the cemented carbide matrix.
[0024] In terms of mass percentage, the content of the second WC powder in the raw material for preparing the cemented carbide substrate of the present invention can be 90% to 95.5%; in a specific embodiment of the present invention, the content of the second WC powder in the raw material for preparing the cemented carbide substrate is 92% or 94%. The mass fraction of carbon in the second WC powder of the present invention can be 6.12% to 6.15%; in a specific embodiment of the present invention, the mass fraction of carbon in the second WC powder is 6.13% or 6.15%. The particle size of the second WC powder of the present invention can be 0.8 to 3.5 μm; in a specific embodiment of the present invention, the particle size of the second WC powder is 2.5 μm or 3 μm.
[0025] The fiber-reinforced cemented carbide of the present invention comprises cemented carbide fibers, and the raw materials for preparing the cemented carbide fibers comprise a first WC powder, a first Co powder and a modifier; in a specific embodiment of the present invention, the raw materials for preparing the cemented carbide fibers consist of a first WC powder, a first Co powder and a modifier.
[0026] In terms of mass percentage, the content of the first Co powder in the raw material for preparing the cemented carbide fiber of the present invention may be 1% to 5% more than the content of the second Co powder in the raw material for preparing the cemented carbide substrate. In a specific embodiment of the present invention, when the content of the second Co powder in the raw material for preparing the cemented carbide substrate is 6%, the content of the first Co powder in the raw material for preparing the cemented carbide fiber is 12%. In another specific embodiment of the present invention, when the content of the second Co powder in the raw material for preparing the cemented carbide substrate is 8%, the content of the first Co powder in the raw material for preparing the cemented carbide fiber is 10%. The particle size of the first Co powder of the present invention may be 1.0 to 1.5 μm; in a specific embodiment of the present invention, the particle size of the first Co powder is 1.0 μm, 1.2 μm or 1.5 μm.
[0027] In terms of mass percentage, the content of the modifier in the raw material for preparing the cemented carbide fiber can be 0.5% to 1.2%; in a specific embodiment of the present invention, the content of the modifier in the raw material for preparing the cemented carbide fiber is 0.8%, 1% or 1.2%. In the present invention, the modifier can be a rare earth oxide; the modifier can include at least one of samarium oxide, yttrium oxide and dysprosium oxide. In a specific embodiment of the present invention, the modifier can be samarium oxide, yttrium oxide or dysprosium oxide. In the present invention, the role of the modifier is to purify the WC grain boundary and strengthen the bonding phase such as cobalt, which is beneficial to simultaneously improve the hardness and toughness of the obtained fiber-reinforced cemented carbide.
[0028] The raw materials for preparing the cemented carbide fiber of the present invention further include a first additive; the first additive may include carbon black, a molding agent and a dispersant. In the present invention, the molding agent may be paraffin; the dispersant may be anhydrous ethanol. The present invention has no special requirements on the specifications of the carbon black and paraffin, and conventional carbon black and paraffin in the art may be used.
[0029] In terms of mass percentage, the content of the first WC powder in the raw material for preparing the cemented carbide fiber of the present invention may be 85% to 90%; in a specific embodiment of the present invention, the content of the first WC powder in the raw material for preparing the cemented carbide fiber is 88% or 89%. The mass fraction of carbon in the first WC powder of the present invention is 0.02% to 0.04% higher than the mass fraction of carbon in the second WC powder. In a specific embodiment of the present invention, when the mass fraction of carbon in the second WC powder is 6.13%, the mass fraction of carbon in the first WC powder is 6.16%. In another specific embodiment of the present invention, when the mass fraction of carbon in the second WC powder is 6.15%, the mass fraction of carbon in the first WC powder is 6.17%. The particle size of the first WC powder of the present invention may be greater than that of the second WC powder by more than 0.5 μm. In a specific embodiment of the present invention, when the particle size of the second WC powder is 3.0 μm, the particle size of the first WC powder is 6.0 μm. In another specific embodiment of the present invention, when the particle size of the second WC powder is 2.5 μm, the particle size of the first WC powder is 4.5 μm.
[0030] The diameter of the cemented carbide fiber of the present invention can be 0.05-0.5 mm, and the aspect ratio can be 2-10; in a specific embodiment of the present invention, the diameter of the cemented carbide fiber is 0.08 mm, 0.1 mm, 0.2 mm or 0.4 mm; the length is 0.4 mm, 0.5 mm, 1 mm or 2 mm. In the fiber-reinforced cemented carbide of the present invention, the mass fraction of the cemented carbide fiber can be 3%-30%; in a specific embodiment of the present invention, the mass fraction of the cemented carbide fiber in the fiber-reinforced cemented carbide is 5%, 10%, 15%, 20% or 25%.
[0031] The present invention relies on cemented carbide fibers to achieve the toughening effect of the cemented carbide matrix. When the cemented carbide matrix generates microcracks and expands, the cracks will deflect or stop when encountering the cemented carbide fibers, thereby achieving the fiber toughening effect. In a specific embodiment of the present invention, the hardness of the cemented carbide fiber is 88.7~90.5HRA, the bending strength is 3078~3126MPa, and the fracture toughness is 15.5~16.2MPa·m 1 / 2 .
[0032] The present invention adopts cemented carbide fiber as toughening material, disperses it in cemented carbide matrix to obtain a fiber-reinforced cemented carbide; since both cemented carbide fiber and cemented carbide matrix belong to WC-Co material system, in this case, fiber-reinforced cemented carbide is prepared, which does not affect the original carbon control system standard, and can solve the problem that the grain boundary is prone to defects due to the mismatch of the interface of dissimilar materials, improve the cemented carbide bonding force, reduce stress, and realize the coordinated densification of two cemented carbides. The fiber-reinforced cemented carbide of the present invention has higher hardness and better toughness at the same time, solves the contradiction between the hardness and toughness of cemented carbide, and further broadens the application field of traditional cemented carbide.
[0033] The present invention also provides a method for preparing the fiber reinforced cemented carbide described in the above technical solution, comprising the following steps: The cemented carbide fiber is mixed with the cemented carbide matrix and sintered to obtain the fiber-reinforced cemented carbide.
[0034] The present invention mixes the raw materials for preparing the cemented carbide fiber and then granulates to obtain the cemented carbide fiber; the present invention does not specifically limit the mixing method of the raw materials for preparing the cemented carbide fiber, and the conventional mixing method in the art can be adopted. In the present invention, after the raw materials for preparing the cemented carbide fiber are mixed, the obtained materials can be ball-milled and dried in sequence. In the present invention, the ball-milling time can be 20-30 hours; the drying can be vacuum drying, the drying temperature can be 80-100°C, and the time can be 4-6 hours. In a specific embodiment of the present invention, the ball-milling time is 25 hours; the vacuum drying temperature is 90°C, and the time is 5 hours. The present invention can granulate the material after ball milling and drying, sieve the obtained material, collect the particles passing through the screen; sinter the particles to obtain the cemented carbide fiber. In the present invention, the granulation can be carried out in a rotary granulator. In the present invention, the aperture of the screen of the rotary granulator can be 0.05-0.5 mm. The sintering of the present invention can be dewaxing sintering; the temperature of the dewaxing sintering can be 1050~1350℃, and the insulation time can be 0.5~1h; in a specific embodiment of the present invention, the temperature of the dewaxing sintering is 1100℃ or 1200℃; the insulation time is 0.5h, 0.8h or 1h.
[0035] The present invention mixes the raw materials for preparing the cemented carbide matrix to obtain the cemented carbide matrix. The present invention does not specifically limit the mixing method of the raw materials for preparing the cemented carbide matrix, and the conventional mixing method in the art can be used. In the present invention, after the raw materials for preparing the cemented carbide matrix are mixed, the obtained materials can be ball-milled to obtain the cemented carbide matrix. In the present invention, the ball-milling time can be 24 to 28 hours. In a specific embodiment of the present invention, the ball-milling time is 24 hours, 26 hours or 28 hours.
[0036] After obtaining the cemented carbide fiber and the cemented carbide matrix, the present invention mixes the cemented carbide fiber with the cemented carbide matrix and sintering to obtain the fiber-reinforced cemented carbide. After mixing the cemented carbide fiber with the cemented carbide matrix, the present invention can sequentially ball mill and dry the obtained materials, sieve the obtained dried materials, and collect the mixture passing through the sieve. In the present invention, the ball milling time can be 2 to 8 hours; the drying can be vacuum drying, the drying temperature can be 60 to 70°C, and the time can be 5 to 7 hours. In a specific embodiment of the present invention, the ball milling time is 2 hours, 4 hours, 6 hours or 8 hours; the vacuum drying temperature is 60°C, 65°C or 70°C, and the time is 5 hours, 6 hours or 7 hours. After obtaining the mixture, the present invention can mold the mixture, sinter the obtained pressed material, and obtain the fiber-reinforced cemented carbide. The present invention has no special requirements for the method and conditions of the compression molding, and the conventional pressing method in the field can be used. In the present invention, the sintering can be pressure sintering; the sintering temperature can be 1400-1450°C, the holding time can be 30-90 minutes, and the pressure can be 1-4MPa; in a specific embodiment of the present invention, the sintering temperature is 1400°C, 1410°C or 1420°C; the holding time is 30 minutes, 45 minutes, 60 minutes or 90 minutes, and the pressure is 1MPa, 2MPa, 3MPa or 4MPa. The present invention prepares the fiber-reinforced cemented carbide by densification through sintering.
[0037] The invention controls the interface composition gradient by designing the composition difference between the cemented carbide fiber and the cemented carbide matrix in the fiber-reinforced cemented carbide, thereby achieving the purpose of synergistic densification and toughening of the two cemented carbides.
[0038] The present invention also provides the use of the fiber-reinforced cemented carbide described in the above technical solution or the fiber-reinforced cemented carbide obtained by the preparation method described in the above technical solution in mining drilling or mold forming.
[0039] The present invention adopts cemented carbide fiber as toughening material, disperses it in a cemented carbide matrix of the same system to obtain a fiber-reinforced cemented carbide, which can achieve coordinated densification of two cemented carbides. The fiber-reinforced cemented carbide has both high hardness and good toughness, which solves the contradiction between hardness and toughness of cemented carbide, and can be used in the fields of mining drilling, mold forming, etc. under certain impact conditions.
[0040] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1 890g WC powder (particle size 6.0μm, carbon black was used to supplement carbon to adjust the mass fraction of carbon in WC powder to 6.17%), 100g Co powder (particle size 1.2μm), 10g samarium oxide, 30g paraffin wax and 240mL anhydrous ethanol were added to the ball mill of a drum ball mill for 25h. After the end, the obtained material was vacuum dried at 90°C for 5h, poured into a rotary granulator with a screen for granulation, and the particles passing through the screen were collected. The particles were dewaxed and sintered at 1200°C for 0.5h to obtain cemented carbide fibers (diameter 0.08mm, length 0.4mm).
[0042] 920g WC powder (particle size is 3.0μm, carbon black is used to supplement carbon to adjust the mass fraction of carbon in WC powder to 6.15%), 80g Co powder (particle size is 1.2μm), 35g paraffin and 280mL anhydrous ethanol are added to the ball mill of the drum ball mill, the ball-to-material ratio is 2:1, ball milling is carried out for 28h, and the cemented carbide matrix slurry is obtained after the ball milling is completed. The cover of the ball mill is opened, and the cemented carbide fiber (the mass ratio of cemented carbide fiber to cemented carbide matrix is 5:95) is placed in the ball mill, and the ball milling is continued for 4h. After the end, the obtained material is vacuum dried at 70℃ for 6h, and the obtained dry material is placed in a sieve with an aperture of 0.375mm for sieving, and the mixture passing through the sieve is collected.
[0043] The mixed material is compression molded, and the obtained pressed material is then constant-temperature sintered at 1420° C. and 3 MPa for 45 minutes to obtain a fiber-reinforced cemented carbide.
[0044] Figure 2 This is a scanning electron microscope image of the fiber reinforced cemented carbide obtained in Example 1.
[0045] Example 2 880g WC powder (particle size 4.5μm, carbon black was used to supplement carbon to adjust the mass fraction of carbon in WC powder to 6.16%), 120g Co powder (particle size 1.0μm), 5g dysprosium oxide, 30g paraffin wax and 240mL anhydrous ethanol were added to the ball mill of a drum ball mill and ball milled for 25h. After the end, the obtained material was vacuum dried at 90°C for 5h, poured into a rotary granulator with a screen for granulation, and the particles passing through the screen were collected. The particles were dewaxed and sintered at 1100°C for 1h to obtain cemented carbide fibers (diameter 0.08mm, length 0.4mm).
[0046] 940g WC powder (particle size is 2.5μm, carbon black is used to supplement carbon to adjust the mass fraction of carbon in WC powder to 6.13%), 60g Co powder (particle size is 1.0μm), 35g paraffin and 280mL anhydrous ethanol are added to the ball mill of the drum ball mill, the ball-to-material ratio is 1.5:1, and the ball milling is carried out for 24 hours. After the end, the cemented carbide matrix slurry is obtained. The cover of the ball mill is opened, and the cemented carbide fiber (the mass ratio of cemented carbide fiber to cemented carbide matrix is 20:80) is placed in the ball mill. The ball milling is continued for 6 hours. After the end, the obtained material is vacuum dried at 70°C for 6 hours, and the obtained dry material is placed in a sieve with an aperture of 0.375mm for sieving, and the mixture passing through the sieve is collected.
[0047] The mixed material is compression molded, and the obtained pressed material is then sintered at a constant temperature of 1410° C. and 4 MPa for 60 minutes to obtain a fiber reinforced cemented carbide.
[0048] Figure 3 This is a scanning electron microscope image of the fiber reinforced cemented carbide obtained in Example 2.
[0049] Comparative Example 1 920 g WC powder (particle size is 3.0 μm, carbon black is used to supplement carbon so that the mass fraction of carbon in WC powder is adjusted to 6.15%), 80 g Co powder (particle size is 1.2 μm), 20 g paraffin and 240 mL anhydrous ethanol are added into the ball mill of a drum ball mill and milled for 32 h. After the milling, the obtained material is vacuum dried at 70 ° C for 6 h, and the obtained dry material is sieved through a sieve with an aperture of 0.375 mm, and the mixture passing through the sieve is collected.
[0050] The mixed material is compression molded, and the obtained pressed material is then sintered at a constant temperature of 1420° C. and 3 MPa for 45 minutes to obtain a cemented carbide.
[0051] Comparative Example 2 940 g WC powder (particle size is 2.5 μm, carbon black is used to supplement carbon so that the mass fraction of carbon in WC powder is adjusted to 6.13%), 60 g Co powder (particle size is 1.0 μm), 20 g paraffin and 240 mL anhydrous ethanol are added into the ball mill of a drum ball mill and milled for 30 h. After the milling, the obtained material is vacuum dried at 70 ° C for 6 h, and the obtained dry material is sieved through a sieve with an aperture of 0.375 mm, and the mixture passing through the sieve is collected.
[0052] The mixed material is molded, and then the obtained pressed material is sintered at a constant temperature of 1410° C. and 4 MPa for 60 minutes to obtain a cemented carbide.
[0053] The fiber reinforced cemented carbides obtained in Examples 1 to 2 and the cemented carbides obtained in Comparative Examples 1 to 2 were tested for hardness, flexural strength and fracture toughness, wherein the test method for hardness refers to GB / T 3849.1-2015 Cemented Carbide Rockwell Hardness Test (A Scale) Part 1: Test Method; the test method for flexural strength refers to GB / T 3851-2015 Cemented Carbide Transverse Fracture Strength Determination Method; the test method for fracture toughness refers to GB / T 23806-2009 Fine Ceramics Fracture Toughness Test Method Single Edge Pre-cracked Beam (SEPB) Method, and the test results are shown in Table 1.
[0054] Table 1 Performance data of the fiber reinforced cemented carbides obtained in Examples 1-2 and the cemented carbides obtained in Comparative Examples 1-2
[0055] As shown in Table 1, compared with Comparative Examples 1-2, the bending strength and hardness of the fiber-reinforced cemented carbide obtained in Examples 1-2 are similar to those of Comparative Examples 1-2, but the fracture toughness is significantly improved. Obviously, the fiber-reinforced cemented carbide obtained in Examples 1-2 has both high hardness and good toughness, solving the contradiction between hardness and toughness of cemented carbide.
[0056] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A fiber reinforced cemented carbide, characterized in that: It includes a cemented carbide matrix and cemented carbide fibers dispersed in the cemented carbide matrix; The raw materials for preparing the cemented carbide fiber include a first WC powder, a first Co powder and a modifier; The raw materials for preparing the cemented carbide substrate include a second WC powder and a second Co powder.
2. The fiber-reinforced cemented carbide according to claim 1, characterized in that: The mass fraction of the cemented carbide fiber in the fiber-reinforced cemented carbide is 3% to 30%; the diameter of the cemented carbide fiber is 0.05 to 0.5 mm, and the aspect ratio is 2 to 10.
3. The fiber-reinforced cemented carbide according to claim 1, characterized in that: In terms of mass percentage, the content of the second Co powder in the raw material for preparing the cemented carbide substrate is 4.5% to 10%.
4. The fiber-reinforced cemented carbide according to claim 1 or 3, characterized in that: The mass fraction of carbon in the second WC powder is 6.12%-6.15%; the particle size of the second WC powder is 0.8-3.5 μm; and the particle size of the second Co powder is 1.0-1.5 μm.
5. The fiber-reinforced cemented carbide according to claim 1, characterized in that: In terms of mass percentage, the content of the first Co powder in the raw material for preparing the cemented carbide fiber is 1% to 5% more than the content of the second Co powder in the raw material for preparing the cemented carbide matrix; and the modifier is a rare earth oxide.
6. The fiber-reinforced cemented carbide according to claim 1 or 5, characterized in that: The modifier includes at least one of samarium oxide, yttrium oxide and dysprosium oxide; the content of the modifier in the raw material for preparing the cemented carbide fiber is 0.5% to 1.2% by mass.
7. The fiber-reinforced cemented carbide according to claim 1, characterized in that: The mass fraction of carbon in the first WC powder is 0.02%-0.04% higher than that in the second WC powder; the particle size of the first WC powder is greater than that of the second WC powder by more than 0.5 μm; and the particle size of the first Co powder is 1.0-1.5 μm.
8. The method for preparing the fiber reinforced cemented carbide according to any one of claims 1 to 7, comprising the following steps: The cemented carbide fiber is mixed with the cemented carbide matrix and sintered to obtain the fiber-reinforced cemented carbide.
9. The preparation method according to claim 8, characterized in that: The sintering temperature is 1400-1450° C., the heat preservation time is 30-90 min, and the pressure is 1-4 MPa.
10. Use of the fiber-reinforced cemented carbide according to any one of claims 1 to 7 or the fiber-reinforced cemented carbide obtained by the preparation method according to any one of claims 8 to 9 in mining drilling or mold forming.
Citation Information
Patent Citations
Cr containing high-grade steel hard alloy cutter material for petroleum pipeline thread machining
CN103911536A
Preparation method and application of reticular structure hard alloy
CN111270121A
Fiber-reinforced hard alloy and preparation method thereof
CN112853236A
Double cemented carbide composites
US5880382A
Diamond coated cutting tools and method of manufacture
US6436204B1